Kinetics and mechanism of proteolytic enzyme catalysed reactions : a thesis presented for the degree of Doctor of Philosophy in Biochemistry - Boland, Michael John (Massey University, 1973)
The enzyme actinidin has been purified and studied chemically and kinetically. The enzyme has many structural and kinetic similarities with ficin and papain. Specificity studies indicate a strong preference for a basic side chain in the S1 site, and competitive inhibitor binding shows a preference for an aromatic group in the S2 site. Inactivation studies show the presence of one active thiol group per enzyme molecule. The hydrolysis of Nα-carbobenzoxy-L-lysine p-nitrophenyl ester by actinidin has been studied in detail. The Michaelis constant, Km, is dependent on groups ionising at pH 3.75 and 8.1. The turnover number, kcat, shows little pH dependence at low pH but an upward inflection dependent on a group ionising at pH 8.1. When the reaction is followed with enzyme concentration in excess of substrate concentration a biphasic reaction is observed. This is interpreted by a mechanism similar to that proposed for ficin and papain catalysed hydrolyses of this substrate. This mechanism is more complicated than the simple acylation-deacylation mechanism normally expected, involving an isomerisation of some kind. Microscopic rate constants for the reaction have been calculated. The significance of various physico-chemical principles of catalysis has been discussed in relation to enzymic catalysis. From a study of the imidazole catalysed hydrolysis of N,O-diacetylserinamide, it has been concluded that general base catalysis could play a much greater part in enzymic catalysis than had previously been estimated.
Keywords: Enzymes; Catalysis